Efficacy and Safety of Qishen Yiqi Dripping Pill for Heart Failure With Preserved Ejection Fraction: A Systematic Review and Meta-Analysis - Wang, Mengxi; Shan, Yiwen; Wu, Chenjie; Cao, Peihua; Sun, Weixin; Han, Jie; Shen, Le; Chen, Jiandong; Yu, Peng; Chen, Xiaohu (Frontiers in Pharmacology, 2021)
Background: The number of heart failure with preserved ejection fraction (HFpEF) patients is increasing year by year, yet all western medicines currently used for heart failure have been shown to be ineffective for HFpEF. Qishen Yiqi Dripping Pill is one of the commonly drugs for the treatment of heart failure in China. In recent years, some clinical studies found that it has curative effect on HFpEF. Objective: To evaluate the efficacy and safety of Qishen Yiqi Dripping Pill in treatment of HFpEF. Methods: Databases including CNKI, Wanfang, VIP, CBM, PubMed, Web of Science, The Cochrane Library and EMbase were searched from their inception to May 2020 to screen relevant randomized controlled trials. The “risk of bias” evaluation tool in the Cochrane Handbook was used to evaluate the quality of the included studies. RevMan 5.3 software was used for meta-analysis. Results: Eight studies meeting the criteria were included, with a total of 895 patients. The results of meta-analysis showed that compared with western medicine alone, combination of western medicine and Qishen Yiqi Dripping Pill can further increase the quotient of early diastolic mitral inflow velocity and late diastolic mitral inflow velocity (E/A) in patients with HFpEF [mean difference (MD)=0.20, 95%CI (0.14, 0.26), P < 0.000 01], decrease the quotient of early diastolic mitral inflow velocity and mitral annular tissue velocity (E/e') [MD=-2.50, 95%CI (-3.18, -1.82), P < 0.000 01], decrease brain natriuretic peptide (BNP) [MD=-151.83, 95%CI (-245.78, -57.89), P=0.002], increase cardiac function improvement rate [relative risk (RR)=1.30, 95%CI (1.11, 1.52), P=0.001], and increase six-minutes walking distance (6-MWD) [MD=64.75, 95%CI (22.65, 106.85), P=0.003]. Four studies reported the occurrence of adverse reactions, among which 3 studies reported no adverse reactions and 1 study reported 3 patients with mild adverse reactions in the intervention group. Conclusion: Qishen Yiqi Dripping Pill is effective and safe in the treatment of HFpEF. However, due to the low quality of the included studies, large heterogeneity among different studies, and high risk of publication bias, the results of our review should be evaluated with prudence. More high-quality clinical studies are needed to verify the conclusion in the future.